PROSPECTS FOR THE DEVELOPMENT OF DIRECT AND INDIRECT TAXATION IN UKRAINE - Шило, Жанна (SWorldJournal, 2022)
The scientific article is devoted to the prospects of direct and indirect taxation in the conditions of uncertainty and crisis in the economy.